Digital innovation in vocational training: utilising mobile augmented reality to enhance learning experiences - Muthu, Nalienaa; Manoharan, Thulasi; Abdul Aziz, Faieza; Abdullah, Lili Nurliyana; Mokhtar, Makhfudzah; Omar, Muhd Khaizer; Win, Lai Lai; Yanjun, Zhou (Universiti Putra Malaysia Press, 2026)
Augmented Reality (AR) has gained significant attention across various domains, aligning with Industry 4.0. Although AR has emerged as a useful tool in various educational applications, its implementation in Technical Vocational Education and Training (TVET) remains underexplored. This study was designed to develop a marker-based AR instructional tool for TVET to enhance technical competencies and learning motivation of trainees, particularly in the microcontroller module. The mobile Augmented Reality for TVET instructional tool was built using Blender 3D, Unity 3D, and Vuforia. There are eight microcontroller components and four simulation circuit assemblies included in the tool. Rasch model was used to assess the validity and reliability of the survey instruments and to ensure uniform functioning of the survey data. Data was collected using the Technology Acceptance Model (TAM) and the Attention, Relevance, Confidence, Satisfaction (ARCS) model to determine usability, engagement and motivation levels. The results obtained from the study shows that 97.4% of the trainees confirm that the mART application is a helpful tool for helping in understanding the microcontroller module. The findings indicate that the mART instructional tools assist trainees in enhancing knowledge retention, engagement and technical skills in TVET education. Since there is a need to bridge the gap between what is being thought in the classrooms and what is obtainable in the field of practice, it implies that, this adoption in the form of AR-based instructional tools is therefore recommended for TVET institutions to ensure the readiness of trainees with industry-oriented skills in the ever-changing and fast developing technological development.